A qualitative investigation of the phenomenology of muscle dysmorphia: Part 2. (March 2023) - Martenstyn, Jordan A.; Maguire, Sarah; Griffiths, Scott
Abstract: Muscle dysmorphia (MD) is a mental disorder characterised by preoccupation that one lacks muscularity and/or leanness, leading to substantial functional impairment. This article is the second of a two-part qualitative study examining the phenomenology of MD among 29 adults with diagnosed MD. We used reflexive thematic analysis to generate five themes which capture the role of exercise in the lives of people with MD. In summary, participants were highly motivated by a constant desire to progress their strength and appearance, and bad or missed workouts which threatened to derail their progress were associated with acute mental health impairment. Most participants scheduled rest days and modified workouts, both for muscle building-related goals and to reduce the risk of injuries, but often continued to exercise when sick. Alongside appearance-driven motivations, participants reported exercising for a variety of non-appearance-related reasons, including to structure their daily lives, boost self-esteem, regulate affect, and gain a sense of control from being able to manipulate their body composition. Exercise was often regarded as a core part of one's identity and overwhelmingly perceived as a net positive behaviour. Sample participant resistance training and cardio routines are described in detail within this article. Highlights: The largest qualitative study to date of individuals with diagnosed MD. Missing or having a bad workout often leads to mood impairment in people with MD. People with MD exercise for a variety of non-appearance-related reasons. There are large individual differences in the way people with MD perceive cardio. People with MD overwhelmingly perceive their exercise as a net positive behaviour.